Sediment genotoxicity in the Tietê River (São Paulo, Brazil): in vitro comet assay versus in situ micronucleus assay studies - Rocha, Paula Suares; Luvizotto, George Luiz; Kosmehl, Thomas; Böttcher, Melanie; Storch, Volker; Braunbeck, Thomas (Ecotoxicology and environmental safety, 2009)
The in vitro comet assay with the permanent fish cell line RTL-W1 and the in situ micronucleus assay using erythrocytes from indigenous tilapia (Oreochromis niloticus) were used to detect genotoxicity in Tietê River sediments (São Paulo, Brazil). Either test was successful in identifying site-specific differences in genotoxicity, with a high correlation between in situ and in vitro results indicating the relevance of the latter even for environmental studies. Discharges from São Paulo city have major impact on genotoxic effects by sediment-bound contaminants; however, overall genotoxicity decreases downstream. The high genotoxic burden of the Tietê River warrants measures to reduce the input of toxic effluents.